1999
DOI: 10.1097/00006216-199902340-00006
|View full text |Cite
|
Sign up to set email alerts
|

Managing Nursing Assets: A Primer on Maximizing Investment in People

Abstract: Nurse managers require critical competencies and skills to thrive in today's turbulent health care environment. A nurse manager's relationship with nursing staff is the primary variable that can reduce nursing turnover and improve unit morale in a variety of measurable ways. Self-confidence is the cornerstone competency required for the nurse manager's success. Nurse managers set the context for the delivery of patient services. To do so effectively, a working partnership with finance and human resources is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Working relationships extended beyond those developed within a "craft" group, with nurses showing improved morale when professional relationships with physicians were viewed as positive. 1 The results showed that when supportive professional relationships with medical staff were present nurses reported that their work was more meaningful and satisfying, their professional knowledge and skills were utilised, and they thought less often of quitting. Additionally, the study suggested that absenteeism and turnover were significantly reduced as a result of a strong sense of community and work-group relationships fostered by the nurse manager.…”
Section: Work Groups/relationshipsmentioning
confidence: 96%
See 1 more Smart Citation
“…Working relationships extended beyond those developed within a "craft" group, with nurses showing improved morale when professional relationships with physicians were viewed as positive. 1 The results showed that when supportive professional relationships with medical staff were present nurses reported that their work was more meaningful and satisfying, their professional knowledge and skills were utilised, and they thought less often of quitting. Additionally, the study suggested that absenteeism and turnover were significantly reduced as a result of a strong sense of community and work-group relationships fostered by the nurse manager.…”
Section: Work Groups/relationshipsmentioning
confidence: 96%
“…The contemporary literature has linked issues such as absenteeism, [1][2][3] retention and recruitment, 4,5 staff turnover, 6,7 and health issues such as increased staff accidents and health risks 8,9 to low morale. As a result of low morale, these poor organisational outcomes are not only costly to the organisation but can also have serious impacts upon the health and wellbeing of staff and, as a consequence, place patients at risk of lower quality care and potentially adverse clinical outcomes.…”
mentioning
confidence: 99%
“…Authors focus on the importance of the ward nurse creating confidence for the nurses on the ward. The ward nurse's relationship with the nurses on the ward is the major variable with regard to the staff's attitudes and morale (Flannery & Grace 1999;Atsalos & Greenwood 2001;Brooks & Swailes 2002). Michie et al (1996) undertook an investigation looking at factors which could contribute to stress among nurses.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It can be argued that the more a nurse is valued for their contribution as part of the health care team the higher the level of morale. The literature draws the link between the nurses’ assessment of their professional worth in the health care system and how that affects morale (Smith 1985, Burda 1992, Flannery & Grace 1999, Livesley 2000, Finlayson 2002).…”
Section: Introductionmentioning
confidence: 99%